Forensic Examination of Orders and Medals - A. Ya. Asnis; Sh. N. Khaziev (Теория и практика судебной экспертизы)
The paper examines the questions of forensic examination of state, departmental and other awards and decorations, including orders, medals and honorary badges. Investigation of such items is usually organized along a comprehensive framework that draws on specialized knowledge from such diverse fields as forensic metal analysis, forensic gemology, historical and cultural analysis, toolmark analysis, and forensic commodity evaluation. Basic methodological provisions are discussed, along with the possibilities of each forensic discipline when applied to the examination of these types of evidence, and required expert qualifications.